Structural deformation control in bridge construction based on error analysis and correction - Juan Li; Rengye Zhao; Shengliang Cao (PLoS ONE, 2025)
Structural deformation control of constructed bridges not only affects the alignment of the bridge, it is also the key to ensure safety. Factors such as temperature and time interval in actual construction can make the bridge deviate from the design state, therefore, this paper proposes a method based on error analysis and correction to eliminate these errors, and realize the structural deformation control in bridge construction control. The cantilever deflection in main girder is modeled and the effect of subsequent cantilevers on deflection at current section is further considered. The error in elevation caused by factors such as temperature and time interval is calculated, and a linear minimum variance estimate is employed to reduce this error. Practical engineering verification is carried out on a bridge in Shanxi, where the proposed error analysis method is further implemented by measuring the current cantilever elevation and comparing it with the original design value, with a purpose of obtaining a reasonable elevation for the next cantilever. The results show that, with the application of error analysis and correction, the elevation error generated during construction process is less than 20 mm, and the elevation error after the completion of bridge is less than 30 mm, the linear shape and internal condition of the bridge structure can also be further conformed to design requirements.